City beyond the city: the notion of contemporary flaneurism in video games - Janik, Justyna (Replay. The Polish Journal of Game Studies, 2015)
This article is a comparative analysis between the exploration video game genre and the theories of contemporary city space. It focuses predominantly on confronting spatial experience of the city space with video game space. This comparison uses the concept of flâneur and slow space to show how these two phenomena are manifested in virtual environments. In the exploration video games, such as "Dear Esther" and "Proteus", the author sees an interesting alternative to overcomplicated gameplay and games overloaded with unnecessary visual information.